Temporal change of urea biochemical transformations and temperature sensitivity of ammonia volatilization in soil textural classes in the brazilian Cerrado - dos Santos Diniz, Mateus Henrique; Ferreira, Fernando César; Ferreira, Adão de Siqueira (Frontiers in Environmental Science, 2025)
IntroductionSoil biochemical transformation of urea has important impacts on nitrogen (N) use efficiency in agricultural systems and environmental pollution, mainly due to N losses through ammonia volatilization (AV).MethodsThe present study aimed to evaluate and model the biochemical transformation of urea and ammonia volatilization in response to different urea doses and temperature conditions over time in sandy loam (SL) and sandy clay loam (SCL) soils in the Brazilian Cerrado. Soil mesocosm experiments were conducted with the addition of 0.25% and 0.50% urea mixed into soils (100 g dry soil) and incubated at 20°C, 25°C, 30°C, and 35°C for six days.ResultsUrease activity increased rapidly on the first day of incubation, with the highest values occurring at the 0.50% urea dose and 25°C. However, there were no significant differences in activity between soils. Soil pH ranged from 8.2 to 8.6 and was not affected by soil type, temperature, or applied doses. Soil ammonium concentration was higher at the 0.50% urea dose and in SCL soil, and it was not affected by temperature conditions. AV increased with the rise in urea dose and temperature, with SL showing higher AV values than SCL. SL also demonstrated greater temperature sensitivity than SCL.DiscussionThe regression equation models used were efficient in demonstrating the parameters of biochemical transformations and AV in both soils. The N losses through AV may be greater than 60% in sandy soils and less than 30% in clay soils.